Database analysis of patients with hepatocellular carcinoma and treatment flow in early and advanced stages. Issue 4 (20th June 2019) - Akada, Keishi; Koyama, Noriyuki; Taniguchi, Shigeru; Miura, Yuji; Aoshima, Ken
Abstract: Despite recent developments in treatment modalities and diagnosis, the prognosis of advanced hepatocellular carcinoma (HCC) remains unsatisfactory. To gain insight into treatment decisions for HCC patients, their characteristics and treatment flow in the early and advanced stages were examined. HCC patients' characteristics and treatment flow were retrospectively analyzed using the Japanese medical claims database. The 8999 patients' mean age at HCC diagnosis was 71.1 years, with no difference between early (Stage I/II) and advanced (Stage III/IV) stages. The mean observation period was 26.2 months, shorter in advanced than in early stages. HCV hepatitis was reported in 52.0% of HCC patients, with concomitant hypertension in 53.4%, type 2 diabetes in 45.8%, cirrhosis in 39.3%, and hyperlipidemia in 15.5%. The rates of HCV hepatitis, hypertension, and hyperlipidemia decreased with stage progression. Analysis of treatment flow showed that, at all disease stages, transcatheter arterial chemoembolization (TACE) was the most common first to fourth‐line treatment. Epirubicin was the most frequently (44.1%) used chemotherapeutic agent for first‐line TACE, followed by miriplatin (23.6%) and cisplatin (12.3%). With stage progression, cisplatin use increased. Sorafenib was used concomitantly for first‐line TACE in 3.2% of patients, and its use increased significantly in advanced stages. Clear differences in baseline characteristics and treatment flow between early and advanced stages were identified. Continuous analysis of the database with longer follow‐up may provide useful information about treatment selection and prediction of outcome such as survival.